Estudo do potencial enzimático hidrolítico e oxidativo do microorganismo Myceliophthora thermophila M.7.7 - Santos, Hévila Brognaro dos [UNESP] (2014)
In terms of the here presented PhD research project the hydrolytic and oxidative enzymatic properties from the ascomycota and themotolerant fungae Myceliophthora thermophila M.7.7. were investigated in detail. Six different secretomes were analysed by mass spectroscopy and 187 proteins were identified. Within these proteins beside already known and expected enzymes also several oxidative active enzymes were confirmed. Enzymes belonging to the cellobiose dehydrogenase and glycoside hydrolase family 7 were most abundant, when in natura and steam exploded sugar cane bagasses were used as carbon source. Particular a high abundance of glycoside hydrolases was identified when a mixture of hemicelluloses was applied as sole carbon source. In this case the secretome analysis showed a substrate-specific secretion for this fungae. The isolation, purification and characterization of a β-glycosidase from M. thermophila M.7.7. showed and confirmed excellent enzymatic charateristics and parameters for future potential applications as a supplemental enzyme in enzyme cocktails, or implimanting by molecular biology in organisms deficient in β-glucosidase. Even at low protein concentration the enzymatic hydrolysis, utilizing the crude extract, resulted in a conversion of approx. 21% in natura bagasse and approx. 16% in commercial cellulose, indicating a high specificity and synergy of the enzyme complex to cellulose polymers with a higher degree of polymerization and crystallinity index in its structure